The Effect of Addition Multi Nutrients Sauce Supplement in Ration on the Consumption of Ration, the Average Daily Gain, and the Conversion of Ration of Rambon Goats - Karina Natasya Juandita; Erwanto Erwanto; Ali Husni; Arif Qisthon (JURNAL ILMIAH PETERNAKAN TERPADU, 2022)
This research aims to study the effect of addition Multi Nutrients Sauce (MNS) supplement in the ration on consumption of ration, the average daily gain (ADG), and conversion of ration of Rambon goats. The research was conducted for 60 days at the farmer of Adi Luwih Hamlet, Adi Jaya Village, TerbanggiBesar District, Central Lampung Regency, Lampung Province. The research was conducted experimentally using the Randomized Block Design method.  Twelve male Rambon goats were grouped into four based on body weight and given three treatments, namely P0 (100% farmer ration), P1 (P0 + 5% MNS), and P2 (P0 + 10% MNS). The data obtained were analyzed for variance and further test of Least Significant Difference (LSD). The results showed that the addition of MNS 5% and 10% in the ration could increase the ration consumption and ADG of Rambon goats (P<0.05), otherwisw, it did not affect the conversion of ration in all treatments (P>0.05).  The ADG and conversion of ration did not different between 5% and 10% MNS, but the ration consumption of 5% MNS was lower than 10% MNS (P<0.05). It was concluded that the addition of 5% MNS could increase body weight gain, but has not been able to increase the efficiency of the ration